Исследование электрических свойств медно-алюминиевых композиций, полученных плакированием взрывом - Загорянский, В. Г.; Дикая, Л. Э. (НТУ "ХПИ", 2015)
В статье исследованы электрические свойства медно-алюминиевых композиций, полученных плакированием взрывом. Получена закономерность влияния отношения толщин слоев биметалла на его удельное электрическое сопротивление. Удельное электрическое сопротивление данного биметалла с отношением толщин слоев меди к алюминию 0,2…0,5 находится между значениями этого параметра для меди и алюминия. Разность между теоретическими и экспериментальными значениями удельного электрического сопротивления при увеличении толщины биметалла возрастает. С увеличением доли плакирующего слоя меди в общей толщине биметалла теоретическое удельное электрическое сопротивление биметалла монотонно понижается, тенденция уменьшения экспериментальных значений также в основном сохраняется, кроме случаев максимальной толщины биметалла.

One of the main directions of the production and consumption of bimetals are traditionally conductor bimetals and contact bimetals based on copper, aluminum and other metals and alloys. In the copper-aluminum bimetal the base layer is made of the cheaper aluminum and having more thickness than a copper cladding layer, serves as a power element. A cladding layer of the more expensive and scarce copper has a somewhat high electrical conductivity. Thus, the bimetal because of the combination of the two conductive layers it is effective as a conductor. At the same time due to surface effects, even at the low proportion of the copper layer thickness of bimetal, bimetal ensures high conductivity and its economy.In the article, the electric properties of copper-aluminum compositions obtained by explosion cladding are investigated. The regularity of effect of the ratio of thickness of layers of the bimetal on its electrical resistivity is obtained. Electrical resistivity of the element, with the ratio of thickness of layers of copper to aluminum of 0.2 to 0.5 is between the values of this parameter for copper and aluminum. Experimental electrical resistivity of metal by increasing the ratio of the thickness of the cladding layer to the total thickness of copper bimetal is more complicated. It can be assumed that the difference arises from the specific to the cladding explosion phenomena – in particular, the formation of intermetallic inclusions and cast molten due to heat in the cladding metal. With increasing thickness of the bimetal the difference increases between the theoretical and experimental values of electrical resistivity. With the increase in the proportion of copper plating layer in the total thickness of the bimetal theoretical electrical resistivity of the sensing element decreases monotonically, the trend of decreasing experimental values are also mostly preserved, except the maximum thickness of the bimetal.
The investigation of electrical properties of copper-aluminum composite obtained by explosion cladding
Keywords: медно-алюминиевый биметалл; отношение толщин слоев; удельное электрическое сопротивление; экономичность; copper-aluminum bimetal; explosion cladding; ratio of thicknesses of layers; specific electrical resistance